(untitled) (World Bulletin of Public Health, 2025)
This article explores the philosophical and legal foundations of reforming and enhancing the social security system in Uzbekistan within the context of developing civil society. The study examines the evolution of social protection mechanisms, the principles of social justice, and the relationship between the state and citizens in ensuring social guarantees. Particular attention is paid to the legal reforms aimed at aligning national legislation with international human rights standards and the growing role of public institutions in shaping an inclusive and equitable social policy. The paper also highlights philosophical concepts of welfare, dignity, and human value that underpin a democratic and people-centered approach to social security. Recommendations are provided for creating a more transparent, fair, and sustainable system that supports vulnerable populations and strengthens civil society institutions in Uzbekistan